Telemedicine in Cardiological Care in Rural Areas: A Review of Implementation Barriers and Efficacy Indicators - Ciesielska, Dominika; Zięba, Natalia; Czech, Mateusz; Cisłak, Miłosz; Chojęta, Michał; Czmok, Jakub; Tarczyński, Dominik; Mazur, Anna; Kociuba, Katarzyna; Brzusek, Mikołaj (Quality in Sport, 2026)
Background: Rural communities are characterized by increased incidence of cardiovascular diseases and higher mortality rates, which result from limited access to specialized medical care. The use of telecardiology technologies allows for the circumvention of geographical barriers through remote monitoring of patients’ vital signs. Aim: The aim of this study is to provide a comprehensive review of clinical effectiveness indicators for telemedicine and to identify systemic, organizational, and socio-demographic barriers hindering its implementation in rural areas. Materials and Methods: This non-systematic review includes studies published in the PubMed database between 2021 and 2025 concerning telemedicine in cardiac care in rural areas. The keywords used included: telemedicine, telehealth, telecardiology, remote patient monitoring, cardiology, cardiovascular care, heart failure, rural health, rural areas, implementation barriers, digital literacy, broadband internet, quality of life, and patient outcomes. Results: Remote care for patients with heart failure reduces the number of readmissions and lowers mortality, resulting in cost savings for the healthcare system. The development of these technologies is hindered by the phenomenon of digital exclusion caused by a lack of broadband connectivity and low technological competence among patients. Additional difficulties stem from challenges with the integration of IT systems and the lack of consistent reimbursement policies. Conclusions: The implementation of telecardiology in the form of integrated hybrid models yields tangible clinical benefits. However, the effective and stable use of remote systems in the long term requires the parallel expansion of local network infrastructure and the application of artificial intelligence algorithms for the automatic verification of incoming telemetry data.